Beach Cleanup: Action to Mitigate Microplastic Waste at Alue Naga Beach, Banda Aceh - Amri, Amri; Zulkifli, Zulkifli; Fadilla, Azura Raihan; Wirda, Shafia; Munawarah, Syirqi Nijam; Hidayat, Wahyu; Arafat, Muhammad Fathin; Anwar, Chairil (Jurnal Pengabdian Bakti Akademisi, 2025)
Alue Naga Beach in Banda Aceh is a coastal area with significant ecological and economic value, but it faces serious threats due to plastic and microplastic pollution. In response to this issue, a beach cleanup initiative was carried out by students from the Development Economics Department of Syiah Kuala University and the Indonesian Language and Literature Education Department of Abulyatama University as part of their community service efforts. The activity was conducted through a hands-on approach on-site, beginning with a site survey, mapping of waste accumulation points, followed by cleanup and documentation of the activity. The results of the activity showed that a total of eight bags of plastic and inorganic waste were successfully collected. Most of the waste consisted of single-use plastic, which has the potential to become a source of microplastics in the ocean. Despite limitations in implementation, the activity successfully contributed positively to beach cleanliness. It is recommended that similar activities be conducted regularly, involving the community, strengthening government support, and incorporating education.